9th Electric Propulsion Conference 1972
DOI: 10.2514/6.1972-489
|View full text |Cite
|
Sign up to set email alerts
|

A 30-cm diameter bombardment thruster with a variable magnetic baffle

Abstract: Thruster performance and stability over a range of beam currents is a function of the hollow cathode propellant flow which depends in part on the baffle geometry. Variable magnetic baffles have been used to allow a change in baffle geometry to Improve thruster performance and stability. Test results of a 30-cm thruster with magnetic baffle are presented. Thruster performance characteristics are analyzed to show how the magnetic baffle field strength can improve performance at a fixed beam current, as well as i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1973
1973
1979
1979

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Slight modifications were also made to the discharge chamber geometry (identical to thruster E-2 in reference 11). The thruster thus incorporates a magnetic baffle circuit with four turns that required a constant-current power supply separate from the power conditioner for the thruster .Tl2, 13) The power conditioning console was initially designed and fabricated by Hughes Research Laboratories under Government contract* 10 ) The system block diagram is shown in Fig. 1.…”
Section: Apparatus and Experimental Technique Thruster And Power Condmentioning
confidence: 99%
“…Slight modifications were also made to the discharge chamber geometry (identical to thruster E-2 in reference 11). The thruster thus incorporates a magnetic baffle circuit with four turns that required a constant-current power supply separate from the power conditioner for the thruster .Tl2, 13) The power conditioning console was initially designed and fabricated by Hughes Research Laboratories under Government contract* 10 ) The system block diagram is shown in Fig. 1.…”
Section: Apparatus and Experimental Technique Thruster And Power Condmentioning
confidence: 99%
“…The magnetic baffle is used to set the cathode flow rate to desired values over the thruster input power range. (15,16) This section discusses alternate methods of controlling the thruster which may allow mission pplanners and power processor designers to perform kradeaf£ studies and improve the overall thrust system properties. Because a ;.arge number of thruster control functions have been required solely for the Purpose of power throttling this section will be divided into two parts: one for a constant thruster operating point; and the other for variable thruster input power.…”
mentioning
confidence: 99%